1996
DOI: 10.1002/j.1460-2075.1996.tb00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane topology and multimeric structure of a mechanosensitive channel protein of Escherichia coli.

Abstract: 4Corresponding author P.Blount and S.I.Sukharev contributed equally to this studyWe have studied the membrane topology and multimeric structure of a mechanosensitive channel, MscL, which we previously isolated and cloned from Escherichia coli. We have localized this 15-kDa protein to the inner membrane and, by PhoA fusion, have shown that it contains two transmembrane domains with both the amino and carboxyl termini on the cytoplasmic side. Mutation of the glutamate at position 56 to histidine led to changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
258
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(275 citation statements)
references
References 48 publications
(22 reference statements)
16
258
1
Order By: Relevance
“…3). When the PhoA domain of the fusion protein remains in the cytoplasm, it does not form the intrachain disulfide bond essential for activity (24), and it becomes sensitive to proteolytic degradation (24,32), as has been reported for PhoA-fusion experiments with other ion transporters (13,25,33). Some of the degradation may have occurred after the cells were broken for making membranes because all of the intact fusion proteins were detected in samples taken from growing E. coli cells (results not shown).…”
Section: Methodsmentioning
confidence: 66%
“…3). When the PhoA domain of the fusion protein remains in the cytoplasm, it does not form the intrachain disulfide bond essential for activity (24), and it becomes sensitive to proteolytic degradation (24,32), as has been reported for PhoA-fusion experiments with other ion transporters (13,25,33). Some of the degradation may have occurred after the cells were broken for making membranes because all of the intact fusion proteins were detected in samples taken from growing E. coli cells (results not shown).…”
Section: Methodsmentioning
confidence: 66%
“…4). Early modelling of the MscL monomer directed a programme of mutagenesis that targeted these same regions (Blount et al, 1996a). Small lesions, such as point mutations, in these regions yielded mutants with altered characteristics, indicating that these regions are crucial to the normal functioning of this channel.…”
Section: Discussionmentioning
confidence: 99%
“…Single-channel analysis E. coli giant spheroplasts were generated and used in patch clamp experiments as described previously (Martinac et al, 1987), with modifications (Sukharev et al, 1994;Blount et al, 1996a). Briefly, excised, inside-out patches were examined at room temperature under symmetrical conditions using a buffer consisting of 200 mM KCl, 90 mM MgCl 2 , 10 mM CaCl 2 and 5 mM HEPES adjusted to pH 6.0.…”
Section: Cloning the Staphylococcus Homologuementioning
confidence: 99%
See 1 more Smart Citation
“…Its 3D structure, unable to be modeled in the first MscL crystal structure reported (24), was revealed in the reinterpreted structure as a single a-helix (139). Several functional studies have demonstrated that even small N-terminal deletions or changes to the N-terminal amino-acid sequence are poorly tolerated, resulting in nonfunctional channels or channels which exhibit altered pressure sensitivity (20,59,143). More recent results suggest that the N-terminus contributes to MscL mechanosensitivity by directly sensing membrane tension and transferring it to the pore lining helices, most likely by maintaining its position along the membranecytoplasm interface (31,68).…”
Section: Structure Of Msclmentioning
confidence: 99%